2002
DOI: 10.1016/s0167-577x(02)00899-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some surfactants on SO2–marble reaction

Abstract: In the polluted atmosphere, sulphur dioxide (SO 2 ) reacts with calcite (CaCO 3 ) in marble producing calcium sulphite hemihydrate (CaSO 3 Á0.5 H 2 O) and gypsum (CaSO 4 Á2H 2 O). Gypsum develops crust at rain-sheltered surfaces and then, being more soluble, accelerates erosion at areas exposed to rain. Eventually, all these lead to significant deformations in the appearance and structure of marble surfaces. Clearly, some precautions must be taken to stop or at least to slow down this deterioration process whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Some previous work showed crystal shapes belonging to calcium sulphate crystals [8,20] and other studies presented calcium sulphite hemihydrate crystals with rough spherical and platelet forms [42,43]. In the present study, it seems that the addition of surfactant molecules (water-repelling admixtures) to the mortar favoured the formation of agglomerates of acicular calcium sulphite hemihydrate crystals.…”
Section: Mortars With Water-repelling Agentssupporting
confidence: 60%
“…Some previous work showed crystal shapes belonging to calcium sulphate crystals [8,20] and other studies presented calcium sulphite hemihydrate crystals with rough spherical and platelet forms [42,43]. In the present study, it seems that the addition of surfactant molecules (water-repelling admixtures) to the mortar favoured the formation of agglomerates of acicular calcium sulphite hemihydrate crystals.…”
Section: Mortars With Water-repelling Agentssupporting
confidence: 60%
“…Furthermore, the deterioration is also the direct result of atmospheric pollution due to soot, grease, dust, etc., implying the deposition of suspended particles on the stonework surface, enhancing the SO 2 deposition, a very reactive compound with a significant corrosive effect on marble surface [15,16]; especially for outdoor monument, anthropogenic factors must be also considered [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the possible ways of slowing down the SO 2 -calcite reaction are producing the less reactive substrate on the marble surface by using some water soluble organic and inorganic compounds such as oleate, oxalate and phosphate ions [12][13][14]. The results of these studies showed that oxalate and oleate anions produced less reactive calcium oxalate and calcium oleate substrate and provided significant protection to marble exposed commonly in sheltered places [13].…”
Section: Introductionmentioning
confidence: 99%